THE PHENOMENON OF CHILDHOOD PSYCHOLOGY THROUGH ARTISTIC IMAGERY: A COMPARATIVE STUDY OF MARK TWAIN AND KHUDOYBERDI TOKHTABOYEV (International journal of artificial intelligence, 2026)
This article examines the typological similarities and national characteristics of artistic imagery in the works of Mark Twain and Khudoyberdi Tokhtaboyev. The authors’ humorous mastery and their principles of using devices such as antithesis and hyperbole are comparatively analyzed.